Simultaneous determination of Ba, Cr, Mo (Group 1), and Cu, Fe, Ni, and Pb (Group 2) in commercial fuel ethanol by graphite furnace AAS - Filho, Volnei Resta Amorim [UNESP]; Caldas, Naise Mary [UNESP]; Júnior, Jorge Luiz Raposo [UNESP]; Flumignan, Danilo Luiz [UNESP]; De Oliveira, José Eduardo [UNESP]; Neto, José Anchieta Gomes [UNESP] (My University, 2008)
The direct and simultaneous determination of Ba, Cr, and Mo (group 1) and of Cu, Fe, Ni, and Pb (group 2) in commercial fuel ethanol by graphite furnace atomic absorption spectrometry is proposed employing no chemical modifier (group 1) and W permanent modifier together with Pd(NO3)2 + Mg(NO3)2 conventional modifiers (group 2). For 20 μL injected volume, the calculated characteristic masses were 65 pg Ba, 3 pg Cr, 13 pg Cu, 10 pg Fe, 43 pg Mo, 50 pg Ni, and 35 pg Pb. The limits of detection (LOD) were 0.6 μg L-1Ba, 0.1 μg L-1 Cr, 0.6 μg L1 Cu, 1.8 μg L-1 Fe, 0.2 μg L-lMo, 0.4 μg L-1 Ni, and 0.6 μg L-1 Pb. Accuracy was checked after the analysis of 10 commercial fuel ethanol samples. The recoveries of Ba, Cr, Cu, Fe, Mo, Ni, and Pb added to the fuel ethanol samples ranged from 100-123%, 84-123%, 85-99%, 90-117%, 81-102%, 89-119%, and 84-114%, and the relative standard deviations (n = 12) were 1.8%, 0.9%, 4.2%, 7.6%, 3.8%, 1.7%, and 2.0%, respectively. The useful lifetimes of the untreated and pretreated tubes were around 300 and 600 firings, respectively.